UJI TOKSISITAS AKUT EKSTRAK ETANOL DAUN KAYU MANIS (Cinnamomum burmanii) PADA FUNGSI HATI TIKUS PUTIH (Mus musculus L.) BETINA - Yesi Nursofia; Fathnur Sani K; Yuliawati Yuliawati (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
Cinnamon leaves (Cinnamomum burmanii) are plants that have many pharmacological effects including lowering blood sugar levels, inhibition of bacterial growth, antioxidants and mymetic insulin activity. However, acute toxicity testing has not been carried out on cinnamon leaves before. This study aims to determine the level of toxicity and effect of extract administration on SGOT, SGPT as well as changes in the histopathological form of the liver of test animals. This study used The Complete Randomized Design method with 5 treatment groups with na-CMC administration 0.5% as a negative control, P1 dose 250 mg/kgBB, P2 Dose 500 mg/kgBB, P3 dose 1000 mg/kgBB and P4 at a dose of 2000 mg/kgBB. Each treatment consists of 5 mice. The parameters observed in this study are SGPT, SGOT and histopathological examination of mice liver organs. The data was analyzed using the One Way ANOVA test with duncan's advanced test. The results showed that the administration of cinnamon leaf ethanol extract did not cause death in test animals so it was practically not toxic. SGPT and SGOT values in female white mice test animals showed statistically meaningful differences in SGPT and SGOT values (p<0.05) compared to negative controls. However, it is still in the normal range. The result of histopathological observations is that there is a change in hepatocytes of liver organs compared to negative control.